2020
DOI: 10.3847/1538-4357/abacc1
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for Wandering Massive Black Holes

Abstract: We investigate low-density accretion flows onto massive black holes (BHs) with masses of ≳105 orbiting around in the outskirts of their host galaxies, performing 3D hydrodynamical simulations. Those wandering BHs are populated via ejection from the galactic nuclei through multibody BH interactions and gravitational wave recoils associated with galaxy and BH coalescences. We find that when a wandering BH is fed with hot and diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 98 publications
4
8
0
Order By: Relevance
“…At high Mach number, the BH accretion rate is expected to be limited to ∼ 10-20% of the canonical Bondi-Hoyle-Lyttleton accretion rate of Eq. (2.1) [66], as shown by recent 3D hydrodynamical simulations. However, the resulting system behavior is sensitive to assumed initial conditions.…”
Section: Bondi-hoyle-lyttleton Accretionsupporting
confidence: 72%
“…At high Mach number, the BH accretion rate is expected to be limited to ∼ 10-20% of the canonical Bondi-Hoyle-Lyttleton accretion rate of Eq. (2.1) [66], as shown by recent 3D hydrodynamical simulations. However, the resulting system behavior is sensitive to assumed initial conditions.…”
Section: Bondi-hoyle-lyttleton Accretionsupporting
confidence: 72%
“…An important caveat for this work is the underlying assumption of Bondi-like accretion, a sub-grid prescription used in most cosmological simulations. Higher resolution simulations have demonstrated that the accretion rate onto wanderers may be limited to ∼ 10 − 20% the Bondi rate due to the wide distribution of angular momentum encountered moving through the halo (Guo et al 2020). Furthermore, if SMBH accretion rates are low enough for their disks to be in the advection dominated regime, then the accumulation of magnetic flux around their horizons may further suppress accretion rates by orders of magnitude (Igumenshchev & Narayan 2002;Perna et al 2003;Pellegrini 2005;Ressler et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that wandering black holes in more massive halos (e.g., the Virgo Cluster) may encounter sufficient gas to be detected via accretion of intercluster medium (e.g., Guo et al 2020). This detection channel is highly unlikely in Milky Way-mass systems.…”
Section: Other Ways To Search For Wandering Black Holesmentioning
confidence: 99%